Boldyrev R.V. Reconstruction of ancient indo-european vocabulary and etymology - Boldyrev R. V. (Philological Treatises, 2020)
This article is dedicated to the investigation of the lexical contacts in coordinates of Indo-European and Afrasian etymology.